Infant anemia: cognitive development and academic performance (2018)
The main objective of the present review study is to determine if anemia has any incidence on cognitive development and academic performance in children. The relevance of the study is justified in the need to address anemia as a global health problem that negatively impacts the entire population, especially the development of children. The research is part of a bibliographical review, of descriptive, retrospective and comparative type, which uses the technique of analysis and interpretation of contents, taking as an information source indexed articles consulted in the databases Springer Link, Scielo, Dialnet, Lilacs and Pubmed, complemented by the non-indexed scientific literature of Google Scholar. The results of the various researches in this topic conclude that iron deficiency anemia is directly related to the performance of children in the school due to iron deficiency causes a significant decrease in brain development and cognitive performance.